Features of the systemic influence of cervical cancer on peripheral blood and hemostasis according to the tumor histological subtype - T. V. Sushinskaya; N. I. Stuklov; E. V. Schepkina; A. I. Kuznetsov; S. V. Еpifanova; A. D. Kaprin (ABV-press, 2024)
Aim. To identify the features of the systemic effect on hematopoiesis and the blood coagulation system of different histological subtypes of cervical cancer (CC).Materials and methods. A single-center retrospective cohort study of 428 patients (61 patients with high grade squamous intraepithelial lesion (carcinoma in situ) and 367 patients with CC) examined from 1997 to 2022 in the Polyclinic of P. Hertzen Moscow Oncology Research Institute - branch of the National Medical Research Radiology Center, Ministry of Health of Russia. The age of patients was from 18 to 90 years (median age - 42 [34; 51] years). Patients were divided into 4 groups: group 1 - patients with high grade squamous intraepithelial lesion and 3 groups depending on tumor's histological subtype (squamous cell, glandular squamous cell, adenocarcinoma). Demographic and clinical data were analyzed including laboratory tests (general blood count, biochemical blood test and iron metabolism and coagulograms (total 32 variables)) compared to clinical and surgical stages of CC.Results. High grade squamous intraepithelial lesion does not have a systemic effect on the parameters of general, biochemical blood tests and hemostasis (p >0.05). On the other hand, statistically significant changes were found in the parameters of routine laboratory blood tests, which correlate with the results of microinvasive analysis of CC, thus revealing the systemic effect of a malignant tumor: at p ≤0.001 for thrombin time, total protein, alkaline phosphatase levels; at p ≤0.05 for alanine aminotransferase, aspartate aminotransferase, C-reactive protein, serum iron and urea levels. Among patients with CC, statistically significant (p<0.001) correlations were obtained between hematological, hemostasiological and biochemical blood parameters. Of statistical significance, the presence of the glandular component in the tumor increases the systemic effect of CC on blood parameters, hemostasis, markers of inflammation and iron metabolism: leukocytosis and maximum erythrocyte sedimentation rate values compared to CC, high fibrinogen and the level of soluble fibrin-monomer complexes which increased activation of coagulation hemostasis along the common coagulation pathway (thrombin time) (p<0.001). It leads to an increase in the risk of venous thromboembolic complications in this category of patients.Conclusion. The identified changes in blood parameters made it possible to reveal the unique biological characteristics of each histological subtype of CC, including biochemical ones, which will help in developing an improved diagnosis of CC depending on the histological subtype and stage of the disease, along with developing preventive measures and treatment methods adapted to each specific case.